Analysis of the Application of Autogenic Relaxation to Pain Management in Hypertension Patients at Royal Prima Medan Hospital in 2026 - Herdy Holandari; Muhammad Habib Asmad; Faridnasra; Muhammad Haikal Lufthy Daulay; Alfonsus Loi; Basri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Hypertension is one of the non-communicable diseases that occurs in the community and can cause various serious complications such as stroke, heart disease, and kidney disorders. One of the complaints that hypertension patients often experience is headache in the nape of the neck due to increased blood pressure. Pain management is not only done pharmacologically, but can also use nonpharmacological therapies such as autogenic relaxation techniques. This study aims to analyze the application of the provision of autogenic relaxation to pain management in hypertension patients at Royal Prima Hospital Medan in 2026. The results showed a decrease in pain levels and blood pressure after autogenic relaxation therapy. On the first day, the patient's blood pressure was 170/90 mmHg with a pain scale of 5, then decreased on the third day to 130/80 mmHg with a pain scale 2. Patients also appear to be more relaxed, less restless, and able to rest better. Final evaluation showed nursing problems of acute pain, activity intolerance, and anxiety could be resolved. The conclusions of this study show that autogenic relaxation techniques are effective in helping to lower headaches and blood pressure in hypertensive patients. This technique can be used as a non-pharmacological supportive therapy in providing nursing care to hypertensive patients.